Shaping history : the role of newspapers in Hawai'i - Chapin, Helen Geracimos (Book collections on Project MUSE., 1996)
Just a decade after the first printing press arrived in Honolulu in 1820, American Protestant missionaries produced the first newspaper in the islands. More than a thousand daily, weekly, or monthly papers in nine different languages have appeared since then. Today they are often considered a secondary source of information, but in their heyday Hawai'i's newspapers formed one of the most diversified, vigorous, and influential presses in the world. In this original and timely work, Helen Geracimos Chapin charts the role Hawai'i's newspapers played in shaping major historic events in the islands and how the rise of the newspaper abetted the rise of American influence in Hawai'i. Shaping History is based on a wide selection of written and oral sources, including extensive interviews with journalists and others working in the newspaper industry. Students of journalism and Hawaiian history will find this comprehensive history of Hawai'i's newspapers especially valuable.